Laminate, package, manufacturing method of laminate, and manufacturing method of package

By using PET containing isophorone diacid in the packaging material and laser treatment to form fragile parts, the problem of uneven laser cutting depth is solved, and the stability of laser cutting and the reliability of packaging material is achieved.

JP2025020322AActive Publication Date: 2025-02-12TOPPAN HOLDINGS INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024194528
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-12
Estimated Expiration
2040-12-15

AI Technical Summary

Technical Problem

During the laser cutting process of existing packaging materials, the difference in cutting depth leads to uneven opening difficulty and required force, and the laser output needs to be adjusted within a high-precision range, increasing manufacturing burden.

Method used

A polymer containing polyethylene terephthalate (PET) and isophorone diacid as diacid units was used to form a fragile portion in combination with laser treatment, and the laser cutting depth and width were controlled by absorbing the laser light between the substrate layer and the thermoplastic sealing layer.

Benefits of technology

It effectively reduces the fluctuation of laser cutting depth, reduces the accuracy requirements of laser output, improves the repeatability and sealing of manufacturing, and simplifies the processing process of packaging materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025020322000001_ABST
    Figure 2025020322000001_ABST
Patent Text Reader

Abstract

To provide a laminate capable of preventing a variation occurring in a depth of a laser processing mark when manufacturing a number of laminates or packages, and also to provide a package, a manufacturing method of a laminate, and a manufacturing method of a package.SOLUTION: A laminate includes a substrate layer 11 containing polyethylene terephthalate and a sealant layer 13 having thermoplasticity. The substrate layer 11 includes a first face 10F being an outermost surface of the laminate. The laminate includes a brittle part 15 linearly extending when viewed from a position facing the first face 10F. The brittle part 15 includes a laser processing mark 16 cut towards an inside of the laminate from the first face 10F. The polyethylene terephthalate includes polyethylene terephthalate containing a terephthalic acid and an isophthalic acid in a dicarboxylic acid unit within a repeating unit.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate for use in a packaging product, a packaging product, a method for manufacturing a laminate, and a method for manufacturing a packaging product. [Background technology]

[0002] Packaging, which is widely used to store various objects such as daily necessities, cosmetics, and medicines, is manufactured from a laminate having a resin base layer and a thermoplastic sealant layer. The sealant layer in the packaging is fused at the periphery of the packaging. The opening guide line that guides the packaging to be torn comprises a fragile portion that is a portion that has been made fragile. Laser processing, in which a cut is made in part of the laminate in the thickness direction from the surface of the base layer toward the inside of the laminate, is used to form the fragile portion (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2019-119457 A Summary of the Invention [Problem to be solved by the invention]

[0004] On the other hand, the occurrence of differences in the depth of the cut when manufacturing a large number of packages results in large differences in the ease of inducing tearing and the force required for tearing between packages. On the other hand, limiting the depth of the cut to a certain range brings about a new excessive manufacturing burden, such as forcing a very high setting value for the laser output itself or forcing a very narrow margin of error in the laser output. [Means for solving the problem]

[0005] A laminate for solving the above problems is a laminate comprising a base layer containing polyethylene terephthalate and a sealant layer having thermoplasticity, wherein the base layer comprises the outermost surface of the laminate, the laminate comprises a weak portion extending linearly when viewed from a position opposite the outermost surface, the weak portion comprises a laser processing mark cutting from the outermost surface toward the inside of the laminate, and the polyethylene terephthalate comprises polyethylene terephthalate containing terephthalic acid and isophthalic acid in dicarboxylic acid units in a repeating unit.

[0006] The packaging body for solving the above problem is a packaging body constructed from a laminate, has a peripheral portion where the sealant layers are fused together, and the fragile portion is positioned at a position in the packaging body that is intended to be opened.

[0007] A method for producing a laminate to solve the above problem includes forming a weak portion in a film laminated with a base layer containing polyethylene terephthalate and a sealant layer having thermoplasticity by irradiating the film with a laser, wherein the polyethylene terephthalate contains polyethylene terephthalate containing terephthalic acid and isophthalic acid in dicarboxylic acid units in a repeating unit, and the film facing the base layer is irradiated with the laser.

[0008] A method for manufacturing a packaging body to solve the above problem includes forming a weak portion in a film laminated with a base layer containing polyethylene terephthalate and a sealant layer having thermoplasticity by irradiating the film with a laser, and fusing the sealant layers together, wherein the polyethylene terephthalate contains polyethylene terephthalate containing terephthalic acid and isophthalic acid in dicarboxylic acid units in a repeating unit, and the laser is irradiated to the film facing the base layer.

[0009] According to the above configurations, it is possible to reduce the variation in the depth of the laser processing mark due to the variation in the laser output. This prevents the laser output from being forced to have an excessively high setting value or an excessively small margin for the laser output error in order to suppress the variation in the depth of the laser processing mark. In addition, the occurrence of variation in the depth of the laser processing mark when manufacturing a large number of laminates or packages is prevented.

[0010] The laminate may further include an intermediate layer sandwiched between the base layer and the sealant layer, and the laser processing mark may include an end portion in the thickness direction of the laminate within the intermediate layer. According to the laminate, it is possible to improve the reproducibility of stopping the end of the laser processing mark inside the intermediate layer without reaching the sealant layer, which makes it possible to suppress the occurrence of variation in the depth of the laser processing mark when manufacturing a large number of laminates and packages, to expand the margin of processing error imposed on the sealing of the package, and to stabilize the sealing property of the package.

[0011] In the laminate, a proportion of isophthalic acid in all dicarboxylic acid units of polyethylene terephthalate contained in the base layer may be 0.5 mol % or more and 5 mol % or less. The laminate described above can also enhance the effectiveness of the effect of mitigating the variation in depth of laser processing marks caused by the variation in laser output.

[0012] In the laminate, the polyethylene terephthalate contained in the base layer may have an intrinsic viscosity of 0.58 dl / g or more and 0.80 dl / g or less. According to the laminate, since the intrinsic viscosity of the polyethylene terephthalate contained in the base layer is 0.58 dl / g or more, it is possible to provide the base layer with the durability and weather resistance required for the package. Also, since the intrinsic viscosity of the polyethylene terephthalate contained in the base layer is 0.80 dl / g or less, it is possible to reduce the process load caused by the handling of raw materials in the manufacturing process of the base layer, such as extrusion, casting, and roll drawing.

[0013] In the above laminate, a width of the laser processing mark may increase from the sealant layer toward the outermost surface. According to the laminate, the width of the laser processing mark increases toward the outermost surface, so that it is easy to irradiate the laser in the direction from the outermost surface toward the sealant layer. In addition, it is easy to recognize the presence of the weak part from a position opposite the outermost surface, so that it is possible to easily handle the weak part by the user of the laminate or package. Effect of the Invention

[0014] According to the present invention, it is possible to suppress the occurrence of variations in the depth of laser processing marks when a large number of laminates or packages are manufactured. [Brief description of the drawings]

[0015] [Figure 1] FIG. 2 is a partial cross-sectional view showing a part of a cross-sectional structure in one embodiment of a laminate. [Diagram 2] FIG. 2 is an enlarged partial cross-sectional view showing a cross-sectional structure of a laminate according to one embodiment. [Diagram 3] FIG. 2 is a plan view showing a planar structure of one embodiment of a packaging body. [Figure 4] FIG. 4 is a process diagram showing an irradiation step in one embodiment of the manufacturing direction of a laminate. [Diagram 5] 1 is a graph showing the relationship between the laser output and the depth of the laser processing mark in the examples. [Figure 6] 4 is a graph showing the relationship between the laser output and the breaking strength of the laminate in the examples. [Figure 7] 1 is a graph showing the relationship between the laser output and the width of the laser processing mark in the examples. [Figure 8] 1 is a graph showing the relationship between the depth of laser processing marks and the breaking strength in the examples. [Figure 9] 1 is a graph showing the relationship between the width of laser processing marks and breaking strength in the examples. [Figure 10] 4 is an optical microscope photograph showing an enlarged cross-sectional structure of a laminate in an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, an embodiment of a laminate, a package, a method for manufacturing a laminate, and a method for manufacturing a package will be described. [Laminate] As shown in FIG. 1, the laminate 10 includes a base layer 11 and a sealant layer 13. The laminate 10 has a first surface 10F, which is a first outermost surface, and a second surface 10R, which is a second outermost surface located on the opposite side to the first surface. The first surface 10F is a surface of the base layer 11, and the second surface 10R is a surface of the sealant layer. The laminate 10 may include an intermediate layer 12. The intermediate layer 12 is sandwiched between the base layer 11 and the sealant layer 13. FIG. 1 shows an example in which the laminate 10 includes the intermediate layer 12.

[0017] The laminate 10 has a fragile portion 15 which is a portion that has been subjected to half-cut processing. Half-cut processing involves irradiating the laminate 10 with a laser, thereby cutting a part of the laminate 10 in the thickness direction. The fragile portion 15 is a portion of the laminate 10 where a laser processing mark is located. The laser processing mark extends linearly when viewed from a position facing the first surface 10F of the laminate 10. The shape of the laser processing mark may be linear or curved. The shape of the laser processing mark may be continuous linear or broken linear. The number of laser processing marks may be one, or may be two or more adjacent to each other.

[0018] The opening of the fragile portion 15 may be located on the first surface 10F or on the second surface 10R. From the viewpoint of suppressing a decrease in the sealing property of the sealant layer 13, it is preferable that the opening of the fragile portion 15 is located on the first surface 10F. The laser irradiated to the laminate 10 may be irradiated in a direction from the base material layer 11 toward the sealant layer 13, or may be irradiated in a direction from the sealant layer 13 toward the base material layer 11. Note that FIG. 1 shows an example in which the laser is irradiated in a direction from the base material layer 11 toward the sealant layer 13, and the laminate 10 has a laser processing mark that opens on the first surface 10F.

[0019] [Base material layer 11] The base material layer 11 has physical properties such as durability and impact resistance required as the outermost layer of a product formed from the laminate 10. The base material layer 11 may be composed of a single layer, or may be a laminate of multiple layers.

[0020] The material constituting the base layer 11 includes recycled PET, which is recycled polyethylene terephthalate (PET). PET products that are subject to recycling include used PET bottles. The recycled PET constituting the base layer 11 is at least one of PET regenerated by mechanical recycling and PET regenerated by chemical recycling.

[0021] In mechanical recycling, PET products are crushed and washed to remove surface dirt and foreign matter, and then the resin is exposed to high temperatures to remove contaminants remaining inside the resin. In chemical recycling, PET products are crushed and washed to remove surface dirt and foreign matter, and then the resin is depolymerized to return to intermediate raw materials, which are then refined and repolymerized to produce PET. From the perspective of reducing the manufacturing cost and environmental load of the base layer 11, it is preferable that the recycled PET contained in the base layer 11 is PET regenerated by mechanical recycling. Compared to chemical recycling, mechanical recycling does not require large-scale equipment for chemical reactions, so the cost and environmental load required for manufacturing recycled PET are small.

[0022] The material constituting the base layer 11 may include virgin PET, which is PET newly synthesized from raw materials such as petroleum, in addition to recycled PET, or may include polyester other than recycled PET. The mass ratio of the recycled PET constituting the base layer 11 is preferably 60% or more and 100% or less of the total mass of the base layer 11.

[0023] The repeating units of PET include diol units and dicarboxylic acid units. The dicarboxylic acid units of recycled PET include terephthalic acid and isophthalic acid. The dicarboxylic acid units of PET constituting the base layer 11 also include terephthalic acid and isophthalic acid. The ratio of isophthalic acid to the total dicarboxylic acid units of PET constituting the base layer 11 is preferably 0.5 mol % or more and 5 mol % or less. If the ratio of isophthalic acid to the total dicarboxylic acid units is 0.5 mol % or more, the effect of softening the base layer 11 and suppressing the propagation of the laser is easily obtained. If the ratio of isophthalic acid to the total dicarboxylic acid units is 5 mol % or less, it is easy to ensure that the base layer 11 has a hardness sufficient to maintain the shape of the laminate 10.

[0024] In addition, when the PET constituting the resin film for packaging use is only virgin PET, the diol unit is ethylene glycol and the dicarboxylic acid unit is terephthalic acid. In contrast, the dicarboxylic acid that is the raw material of the PET constituting the PET bottle contains isophthalic acid in addition to terephthalic acid in order to improve the processability of the resin when molding the bottle. The dicarboxylic acid unit of the PET constituting the PET bottle also contains terephthalic acid and isophthalic acid. Isophthalic acid shortens the main chain of the PET compared to PET consisting of only terephthalic acid, suppresses crystallization of the PET, and improves the processability of the PET. In addition, the diol unit of the PET constituting the PET bottle may contain diethylene glycol in addition to ethylene glycol, or may be only ethylene glycol.

[0025] The average molecular weight of the PET constituting the base layer 11 is not particularly limited, but is preferably, for example, from 1,000 to 1,000,000. The material constituting the base layer 11 may contain various additives such as resins other than PET and plasticizers.

[0026] The intrinsic viscosity of the PET constituting the base layer 11 is preferably 0.58 dl / g or more and 0.8 dl / g or less. If the intrinsic viscosity of the polyethylene terephthalate contained in the base layer 11 is 0.58 dl / g or more, it is possible to obtain the durability and weather resistance required for the packaging body in the base layer 11. In addition, since the intrinsic viscosity of the polyethylene terephthalate contained in the base layer 11 is 0.80 dl / g or less, it is possible to reduce the process load caused by the handling of raw materials in the manufacturing process of the base layer 11, such as extrusion, casting, and roll stretching.

[0027] The material constituting the base material layer 11 may contain polyester other than recycled PET and virgin PET. The polyester other than recycled PET and virgin PET has, for example, a chain aliphatic carboxylic acid or a cyclic aliphatic carboxylic acid as a carboxylic acid unit. The material constituting the base material layer 11 may contain additives other than polyester. The additives are, for example, a color inhibitor, an antistatic agent, a weathering agent, an ultraviolet absorbing agent, a deodorizer, an antioxidant, etc.

[0028] The first surface 10F of the base layer 11 may be provided with an anchor coat layer made of an anchor coat agent, or a printed layer formed by printing, such as letters, figures, symbols, patterns, etc. In addition, the surface of the base layer 11 opposite to the first surface 10F may also be provided with a printed layer, or may be subjected to a surface treatment to enhance adhesion with other adjacent layers. In addition, the surface of the base layer 11 may be provided with.

[0029] The thickness of the base layer 11 is preferably 3 μm or more and 50 μm or less, and more preferably 10 μm or more and 30 μm or less. If the thickness of the base layer 11 is 3 μm or more, the durability and impact resistance of the base layer 11 can be obtained. In addition, if the thickness of the base layer 11 is 50 μm or less, the processability of the laminate 10 including the base layer 11 can be improved.

[0030] The base layer 11 can be formed by a known film forming method such as extrusion molding. The cooling in the extrusion molding can be performed by a known method such as cooling roll, air cooling, or water cooling. The base layer 11 may be a stretched film or a non-stretched film. The base layer 11 can be stretched by a known method such as uniaxial stretching or biaxial stretching.

[0031] [Sealant layer 13] The sealant layer 13 is a layer that allows heat fusion between one part of the sealant layer 13 and another part of the sealant layer 13. The sealant layer 13 may be composed of a single layer, or may be a laminate of multiple layers. When the sealant layer 13 has multiple layers, the layers constituting the sealant layer 13 may have the same composition, or the constituent layers of the sealant layer 13 may include layers with different compositions.

[0032] The material constituting the sealant layer 13 may be a linear polyolefin or a cyclic polyolefin. The linear polyolefin is, for example, an ethylene-based resin, a propylene-based resin, an ethylene-propylene copolymer, or an ester of an ethylene-α,β-unsaturated carboxylic acid copolymer. The cyclic polyolefin is, for example, a ring-opening metathesis polymer (COP) of a cyclic olefin, or a cyclic olefin copolymer (COC). The material constituting the sealant layer 13 may contain an additive such as a light-shielding agent.

[0033] The thickness of the sealant layer 13 is preferably 20 μm or more and 100 μm or less, and more preferably 30 μm or more and 70 μm or less. If the thickness of the sealant layer 13 is 20 μm or more, it is possible to obtain sufficient sealing properties by the sealant layer 13. If the thickness of the sealant layer 13 is 100 μm or less, it is possible to improve the processability of the laminate 10 including the sealant layer 13.

[0034] [Middle layer 12] The intermediate layer 12 may be a barrier layer that suppresses the transmission of oxygen and water vapor, or a reinforcing layer that enhances the impact resistance and mechanical toughness of the laminate 10. The intermediate layer 12 may also be a light-shielding layer that blocks the transmission of light, or a printed layer on which printing has been performed. The variation in the depth of the laser processing mark may also occur in the laminate 10 including the intermediate layer 12, whether the intermediate layer 12 is capable of absorbing a laser or capable of reflecting a part of a laser, such as when the substrate layer 11 is not penetrated by the laser processing or when processing is stopped inside the intermediate layer 12. Among these, the variation in the depth of the laser processing mark is particularly significant in a configuration including an intermediate layer 12 that can absorb a laser, and therefore the suppression of variation by including the above-mentioned substrate layer 11 is particularly effective in the laminate 10 including an intermediate layer 12 that can absorb a laser.

[0035] The barrier layer may be a metal foil such as aluminum foil. The barrier layer may be a vapor-deposited film of a metal such as aluminum, tin, chromium, or nickel, or a vapor-deposited film of an inorganic oxide such as silicon oxide, aluminum oxide, titanium oxide, or zirconium oxide. The barrier layer may be a resin film made of a saponified ethylene-vinyl acetate copolymer.

[0036] The reinforcing layer may be a nylon film such as 6-nylon, 6,6-nylon, 11-nylon, or 12-nylon, or may be a copolymer nylon film that is a copolymer of 6-nylon and 6,6-nylon. The light-shielding layer is, for example, a resin layer containing a light-shielding pigment. Examples of the light-shielding pigment include carbon black, graphite, aniline black, titanium oxide, barium oxide, aluminum hydroxide, and zinc oxide.

[0037] A known method can be used for laminating the base layer 11 and the intermediate layer 12, laminating the intermediate layer 12 and the sealant layer 13, or laminating the base layer 11 and the sealant layer 13 without the intermediate layer 12. The method for laminating each layer may be, for example, a dry lamination method, an extrusion lamination method, or a sandwich lamination method using the extrusion lamination method. A known adhesive for lamination can be used as the adhesive used in the dry lamination method. The adhesive for lamination is, for example, any one selected from the group consisting of polyurethane-based, polyacrylic-based, polyester-based, epoxy-based, polyvinyl acetate-based, and cellulose-based adhesives.

[0038] [Weakened part 15] The structure of the fragile portion 15 will be described with reference to Fig. 2. The laser processing mark 16 constituting the fragile portion 15 is a cut extending from the first surface 10F toward the inside of the laminate 10. The groove bottom of the laser processing mark 16 is an end 16E located on the second surface 10R side of the two ends that the laser processing mark 16 has in the thickness direction of the laminate 10. The opening of the laser processing mark 16 is located on the opposite side to the end 16E of the two ends that the laser processing mark 16 has in the thickness direction of the laminate 10.

[0039] The end 16E of the laser processing mark 16 may be located inside the base material layer 11, may be located inside the sealant layer 13, or may be located inside the intermediate layer 12. The end 16E of the laser processing mark 16 may be located in the same layer in the direction in which the laser processing mark 16 extends, or may be located in different layers. From the viewpoint of improving the sealing ability of the sealant layer 13, it is preferable that the end 16E of the laser processing mark 16 is located inside the base material layer 11 or the intermediate layer 12. From the viewpoint of improving the openability using the fragile portion 15, it is preferable that the end 16E of the laser processing mark 16 is located inside the intermediate layer 12.

[0040] The strength of the fragile portion 15 is preferably high enough to prevent the fragile portion 15 from breaking due to vibration or the like before the package is opened, and low enough to easily break due to an external force such as the force of the user's hand when the package is opened. From the viewpoint of easily obtaining a toughness that satisfies these requirements, it is preferable that the laminate 10 has an intermediate layer 12, and the end 16E is located within the intermediate layer 12. Furthermore, it is preferable that the end 16E is located within the same intermediate layer 12 in the direction in which the laser processing mark 16 extends throughout the entire laser processing mark 16. Note that FIG. 2 shows an example in which the end 16E of the laser processing mark 16 is located within the intermediate layer 12.

[0041] The fragile portion 15 may have a raised portion 17 that continues in the extension direction of the laser processing mark 16 at each of both ends in the width direction of the laser processing mark 16. The raised portion 17 is a portion where both ends in the width direction of the laser processing mark 16 locally rise at the edge of the opening. When the opening of the laser processing mark 16 is located on the first surface 10F, the raised portion 17 is also located on the first surface 10F. When the laser processing mark 16 is formed by irradiating a laser, the base material layer 11 melts due to heat generated by the base material layer 11 absorbing the laser light. A part of the melted base material layer 11 moves to the side of the laser processing mark 16, and as a result, the raised portion 17 is formed. The fact that the laser processing mark 16 has the raised portion 17 helps to visually and tactilely grasp the presence of the fragile portion 15.

[0042] The length of the laser processing mark 16 in the width direction gradually increases in the direction from the sealant layer 13 toward the base layer 11. The maximum width W of the laser processing mark 16 is the width direction length of the gap between the two raised portions 17. The degree to which the length of the laser processing mark 16 in the width direction increases per unit thickness may increase, be constant, or decrease in the direction from the sealant layer 13 toward the base layer 11. Note that FIG. 2 shows an example in which the length of the laser processing mark 16 in the width direction increases per unit thickness in the direction from the sealant layer 13 toward the base layer 11.

[0043] The difference between the thickness T of the laminate 10 and the length X along the thickness direction from the end 16E to the second surface 10R is the depth of the laser processing mark 16. The thickness T of the laminate 10 is the total thickness of the laminate 10 in the portion where the fragile portion 15 is not formed. From the viewpoint of improving the sealability of the product formed using the laminate 10, it is preferable that the depth of the laser processing mark 16 does not reach the sealant layer 13. Furthermore, when the laminate 10 has a barrier layer as the intermediate layer 12, it is preferable that the depth of the laser processing mark 16 does not reach the barrier layer from the viewpoint of suppressing a decrease in the barrier property of the laminate 10.

[0044] As described above, the occurrence of differences in the depth of the laser processing marks 16 during the production of a large number of laminates 10 or packages results in significant variations in the ease of tear induction and the force required for tearing between products. On the other hand, limiting the depth of the laser processing marks 16 to a certain range brings about a new excessive manufacturing burden, such as forcing a very high setting value for the laser output itself or forcing a very narrow margin of error in the laser output.

[0045] When the base layer 11 has a plurality of layers, the compositions of the layers constituting the base layer 11 may be the same, or the layers constituting the base layer 11 may include layers of different compositions. The layers constituting the base layer 11 may include a layer made of recycled PET and a layer made of virgin PET. The layers constituting the base layer 11 may include a plurality of layers containing recycled PET in different proportions. The depth of the laser processing mark 16 has small variation in the layer made of recycled PET and large variation in the layer made of virgin PET. From the viewpoint of suppressing the variation in the depth of the laser processing mark 16, it is preferable that the layer made of recycled PET is closer to the opening of the laser processing mark 16 than the layer made of virgin PET.

[0046] When the base material layer 11 includes the intermediate layer 12, the absorptance of the laser irradiated to the laminate 10 may be higher in the base material layer 11 than in the intermediate layer 12, or may be higher in the intermediate layer 12 than in the base material layer 11. When a laser is irradiated from the base material layer 11 toward the sealant layer 13, it is preferable that the absorptance of the base material layer 11 is higher than that of the intermediate layer 12, from the viewpoint of suppressing variation in the depth of the laser processing marks 16.

[0047] Processing proceeds in order from the layer with the highest laser absorption rate, which is preferable from the viewpoint of suppressing variations in depth at the end of processing, since the processing speed slows down as the laser irradiation proceeds.

[0048] [Package 20] A package is manufactured using the laminate described above. Examples of the package include a side-sealed package, a two-sided sealed package, a three-sided sealed package, a four-sided sealed package, an envelope-sealed package, a pillow-sealed package, a pleated sealed package, a flat-bottom sealed package, and a square-bottom sealed package. Other examples of the package include a one-piece package, a two-piece package, and packages with other spouts or zippers for opening and closing. Other examples of the package include a self-supporting package, a tube container, and a liquid-filled paper container including a paper base layer.

[0049] Examples of contents that the packaging can hold include various foods and beverages including fruit juice, juice, drinking water, alcohol, cooked foods, fish paste products, frozen foods, meat products, simmered dishes, rice cakes, liquid soup, condiments such as soy sauce and sauces, and fresh sweets, as well as non-food items including liquid detergents, cosmetics, and chemical products.

[0050] A three-sided sealed package, which is an example of a package, will be described with reference to Fig. 3. The package 20 is in the shape of a bag formed from the laminate 10 and is configured to be sealable. In the package 20, the base layer 11 is located outside the sealant layer 13. Ends of the sealant layer 13 are joined together on three sides of the package 20. The portion where the ends of the sealant layer 13 are joined together is a sealed portion 21 of the package 20.

[0051] The sealed portion 21 has an opening start portion 22. The opening start portion 22 is a cutout extending from a portion of the periphery of the sealed portion 21 toward the inside of the sealed portion 21. The package 20 has an opening guide line 23 extending in one direction from the opening start portion 22. The opening guide line 23 connects two opposing sides of the sealed portion 21, which are the three sides of the package 20. The opening start portion 22 is one end portion of the opening guide line 23.

[0052] The opening guide line 23 is a portion that imparts partial weakness to the package 20. The opening guide line 23 is a weak portion 15 formed in the laminate 10. The opening guide line 23 may be formed before the sealing portion 21 is formed, or may be formed after the sealing portion 21 is formed. When the package 20 is opened, a tear in the laminate 10 that starts from the opening initiation portion 22 advances along the opening guide line 23 and does not deviate from the opening guide line 23.

[0053] [Manufacturing method] The method for producing the laminate includes (A) laminating the sealant layer 13 on the base layer 11, and (B) irradiating the laminate 10 with a laser to form laser processing marks 16. The method for producing the packaging body includes (A) laminating the sealant layer 13 on the base layer 11, (B) irradiating the laminate 10 with a laser to form laser processing marks 16, and (C) heat-sealing the sealant layers 13 together.

[0054] (A) Laminating the sealant layer 13 on the base material layer 11 includes, in the case where the laminate 10 includes an intermediate layer 12, laminating the intermediate layer 12 on the base material layer 11, and laminating the sealant layer 13 on the intermediate layer 12. Alternatively, (A) Laminating the sealant layer 13 on the base material layer 11 includes laminating the sealant layer 13 on the intermediate layer 12, and laminating the intermediate layer 12 and the base material layer 11 together.

[0055] The method for laminating the base material layer 11 and the sealant layer 13, the method for laminating the base material layer 11 and the intermediate layer 12, and the method for laminating the intermediate layer 12 and the sealant layer 13 may each be a dry lamination method, an extrusion lamination method, a cast molding method, or a T-die method.

[0056] In addition, when the first surface 10F is an anchor coat layer, the anchor coat layer may be laminated onto the base material layer 11 before the base material layer 11 and the sealant layer 13 are laminated together, or the anchor coat layer may be laminated onto the base material layer 11 after the base material layer 11 and the sealant layer 13 are laminated together.

[0057] Furthermore, when the first surface 10F has a printed layer, the printed layer may be laminated onto the first surface 10F before the base material layer 11 and the sealant layer 13 are laminated together, or the printed layer may be laminated onto the first surface 10F after the base material layer 11 and the sealant layer 13 are laminated together.

[0058] In addition, when a printed layer is provided on the surface of the base material layer 11 opposite the first surface 10F, the printed layer is formed on the base material layer 11 before laminating the base material layer 11 and the sealant layer 13, or before laminating the base material layer 11 and the intermediate layer 12.

[0059] (C) Heat fusing the sealant layers 13 together forms the sealed portion 21. The types of heat seal for forming the sealed portion 21 include, for example, a side seal type, a two-sided seal type, a three-sided seal type, a four-sided seal type, an envelope-pasted seal type, a pillow seal type, a pleated seal type, a flat-bottom seal type, and a square-bottom seal type. The method for forming the sealed portion 21 includes, for example, a bar seal, a rotary roll seal, a belt seal, an impulse seal, a high-frequency seal, and an ultrasonic seal.

[0060] In one example of forming the sealing portion 21, one laminate 10 having a rectangular shape is used. One laminate 10 is folded in half so that the sealant layers 13 of the laminate 10 are in contact with each other. Next, the sealant layers 13 on three sides of the folded laminate 10 are heat-sealed to produce a three-sided sealed package 20.

[0061] Another example of forming the sealing portion 21 uses two rectangular laminates 10. The two laminates 10 are stacked such that the sealant layers 13 located on the four sides of the two laminates 10 are in contact with each other. The sealant layers 13 located on the four sides are heat-sealed to produce a four-sided sealed package 20.

[0062] Another example of forming the sealing portion 21 uses one laminate 10 having a rectangular shape. The laminate 10 is bent into a cylindrical shape so that the sealant layer 13 of one laminate 10 is on the inside. The sealant layers 13 located at the connection parts of the cylindrical surface are heat-sealed to each other to form a back-attaching portion, which is an example of the sealing portion 21. Furthermore, the sealant layers 13 located at the upper and lower openings of the cylindrical surface are heat-sealed to each other to manufacture the remaining part of the sealing portion 21.

[0063] (B) Forming the laser processing marks 16 by irradiating the laminate 10 with a laser is to form the fragile parts 15 or the opening guide lines 23. 4, a laser may be irradiated by a laser head 50 from the base material layer 11 toward the sealant layer 13, or from the sealant layer 13 toward the base material layer 11. The laser absorbed by the base material layer 11 melts a part of the base material layer 11 to form a laser processing mark 16. The base material layer 11 irradiated with the laser absorbs the laser light and generates heat. The part of the base material layer 11 that melts due to the heat generates a notch and also forms a raised portion 17 near the edge of the laser spot.

[0064] The wavelength range of the laser is included in the wavelength range absorbed by the base layer 11. The wavelength range absorbed by the base layer 11 may be an infrared wavelength range or a near-infrared wavelength range. From the viewpoint of being more easily absorbed by PET than nylon-based resins and polypropylene-based resins, the wavelength range of the laser is preferably 700 nm or more and 2000 nm or less, and more preferably 900 nm or more and 1100 nm or less. The laser head 50 may be a continuous oscillation carbon dioxide gas laser head or a pulse oscillation carbon dioxide gas laser head. In addition, the laser head 50 may be a continuous oscillation YAG laser head or a pulse oscillation YAG laser head.

[0065] The spot diameter of the laser output by the laser head 50 and the average output of the laser head 50 are appropriately set according to the depth and width required for the laser processing marks 16. The laser spot diameter is a Gaussian beam diameter. The average output of the laser head 50 is set by the output % in the laser output conditions. For example, when the laser head 50 has a maximum output of 30W and is set to 50% output, the average output of the laser head 50 is 15W.

[0066] The spot diameter of the laser is, for example, 1 μm to 500 μm, and preferably 2 μm to 100 μm. The average output of the laser head 50 is, for example, 5 W to 50 W, and preferably 10 W to 30 W.

[0067] From the viewpoint of suppressing the occurrence of variation in the depth of the laser processing mark 16, it is preferable that the scanning speed of the laser head 50 is constant throughout the period in which the laser processing mark 16 is formed. The scanning of the laser head 50 may be performed by scanning the laser head 50 with respect to the laminate 10, or by scanning the laminate 10 with respect to the laser head 50, or a combination of these. By slowing down the scanning speed of the laser head 50, the depth of the laser processing mark 16 can be made deeper. Conversely, by increasing the scanning speed of the laser head 50, the depth of the laser processing mark 16 can be made shallower. The scanning speed of the laser head 50 is, for example, 200 m / min or less, and preferably 100 m / min.

[0068] Forming the laser processing mark 16 may include extracting a part of the laminate 10 and inspecting the appearance of the laser processing mark 16 using various optical inspection devices in order to inspect the shape of the laser processing mark 16. Forming the laser processing mark 16 may also include extracting a part of the laminate 10 and inspecting the tensile breaking strength of the laminate 10 in order to inspect the properties of the laser processing mark 16.

[0069] [Example 1] The laminate 10 of Example 1 was produced by dry lamination using the following films as the base layer 11, intermediate layer 12, and sealant layer 13. The proportion of isophthalic acid in the total dicarboxylic acid units of the PET contained in the base layer 11 of Example 1 is 0.5 mol % or more and 5 mol % or less. The intrinsic viscosity of the PET contained in the base layer 11 of Example 1 is 0.58 dl / g or more and 0.80 dl / g or less.

[0070] Hereinafter, PET film will be referred to as "PET", nylon film as "Ny", non-oriented polypropylene film as "CPP", and biaxially oriented polypropylene film as "OPP". A two-component curing aliphatic ester-based dry lamination adhesive (main agent product name: Takelac (registered trademark) A-626 / hardener product name: Takenate (registered trademark) A-50, manufactured by Mitsui Chemicals, Inc.) was used to bond each layer.

[0071] Base layer 11: Recycled PET (thickness 12 μm / product name: R8100, manufactured by Toyobo Co., Ltd.) Intermediate layer 12: Ny (thickness 15 μm / product name: Bonyl (registered trademark)-W, manufactured by Kohjin Film & Chemicals Co., Ltd.) Sealant layer 13: CPP (thickness 50 μm / product name: FHK2, manufactured by Futamura Chemical Co., Ltd.)

[0072] [Comparative Example 1] The laminate 10 of Comparative Example 1 was produced using the following films as the base layer 11, intermediate layer 12, and sealant layer 13. The same aliphatic ester-based dry lamination adhesive as in Example 1 was used to bond the layers. Base layer 11: Virgin PET (thickness 12 μm / product name: E5100, manufactured by Toyobo Co., Ltd.) Intermediate layer 12: Ny (thickness 15 μm / product name: Bonyl (registered trademark)-W, manufactured by Kohjin Film & Chemicals Co., Ltd.) Sealant layer 13: CPP (thickness 50 μm / product name: FHK2, manufactured by Futamura Chemical Co., Ltd.)

[0073] [Comparative Example 2] The laminate 10 of Comparative Example 2 was produced using the following films as the base layer 11, intermediate layer 12, and sealant layer 13. The same aliphatic ester-based dry lamination adhesive as in Example 1 was used to bond the layers. Base layer 11: OPP (thickness 20 μm / product name: FOR, manufactured by Futamura Chemical Co., Ltd.) Intermediate layer 12: Ny (thickness 15 μm / product name: Bonyl (registered trademark)-W, manufactured by Kohjin Film & Chemicals Co., Ltd.) Sealant layer 13: CPP (thickness 50 μm / product name: FHK2, manufactured by Futamura Chemical Co., Ltd.)

[0074] [Comparative Example 3] The laminate 10 of Comparative Example 3 was produced using the following films as the base layer 11, intermediate layer 12, and sealant layer 13. The same aliphatic ester-based dry lamination adhesive as in Example 1 was used to bond the layers. Base layer 11: Ny (thickness 15 μm / product name: Emblem (registered trademark) ON, manufactured by Unitika Ltd.) Intermediate layer 12: Ny (thickness 15 μm / product name: Bonyl (registered trademark)-W, manufactured by Kohjin Film & Chemicals Co., Ltd.) Sealant layer 13: CPP (thickness 50 μm / product name: FHK2, manufactured by Futamura Chemical Co., Ltd.)

[0075] [evaluation] The laminate 10 of Example 1 and each Comparative Example was subjected to laser processing using the following output conditions. At this time, the laminate 10 was wound around a roll, and the laser was irradiated on the outermost surface of the rotating roll-shaped raw roll, thereby scanning the laser along the MD direction of the base layer 11 and the intermediate layer 12. Six different positions in the axial direction of the roll were set as the laser irradiation positions. That is, six weak parts 15 were formed on each of the raw rolls of Example 1 and each Comparative Example. Then, the laser processing marks 16 were observed using a scanning electron microscope, and the width and depth of the laser processing marks 16 were measured, and the average values ​​of the six weak parts 15 in Example 1 and each Comparative Example were set as the width and depth of the laser processing marks 16 in the example. [Output conditions] Head: Carbon dioxide laser head (product name: ML-Z9510, manufactured by Keyence Corporation) ·Wavelength range: 10.6μm Average laser power: 10W to 35W Scanning speed: 80m / min Spot diameter: 2μm

[0076] Furthermore, for the laminates 10 of Example 1 to Comparative Example 3 after laser processing, the tensile breaking stress in the TD direction of the fragile parts 15 was measured using a tensile tester, and the average value of the six fragile parts 15 in each example was taken as the breaking strength for that example. The tensile breaking stress was measured using a method conforming to "Plastics - Test methods for tensile properties - Part 3: Test conditions for films and sheets" of JIS K7127:1999 (ISO 527-3:1995) and "Plastics - Determination of tensile properties - Part 1: General rules" of JIS K7161-1:2014 (ISO 527-1:2012), and the following conditions are shown below. [Measurement conditions] ·Distance between gauge lines: 50mm Test speed: 100mm / min

[0077] FIG. 5 shows the relationship between the average output and the depth of the laser processing mark 16 in Example 1 together with the results of Comparative Examples 1 to 3. FIG. 6 shows the relationship between the average output and the breaking strength in Example 1 together with the results of Comparative Examples 1 to 3. FIG. 7 shows the relationship between the average output and the width of the laser processing mark 16 in Example 1 together with the results of Comparative Examples 1 to 3. FIG. 8 shows the relationship between the depth of the laser processing mark 16 in Example 1 together with the results of Comparative Examples 1 to 3. FIG. 9 shows the relationship between the width of the laser processing mark 16 in Example 1 together with the results of Comparative Examples 1 to 3. And FIG. 10 is an optical microscope photograph showing the cross-sectional structure of the laminate of Example 1, and shows a structure corresponding to FIG. 2.

[0078] 5, the depth of the laser processing marks 16 in the laminate 10 of Example 1 was 21 μm or more and 18 μm or less, with only a slight difference of about 3 μm. It was also found that the laser processing marks 16 reached the intermediate layer 12 at an average output of 20 W. It was found that the depth of the laser processing marks 16 slightly decreased as the average laser output increased from 20 W to 32 W, but the decrease was almost negligible, and it can be said that the depth was approximately constant with respect to the change in the average output.

[0079] In contrast, the depth of the laser processing marks 16 in the laminate 10 of Comparative Example 1 was found to be 14 μm or more and 24 μm or less, with a difference of about 10 μm. Note that, also in Comparative Example 1, it was found that the laser processing marks 16 reached the intermediate layer 12 when the average output was 20 W. It was also found that the depth of the laser processing marks 16 showed a larger value as the average laser output increased from 20 W to 32 W.

[0080] Moreover, it was found that the depth of the laser processing marks 16 in the laminate 10 of Comparative Example 2 was 0 μm or more and 24 μm or less, with a difference of 24 μm or more. In Comparative Example 2, it was found that at an average output of 10 W, the laser processing marks 16 were hardly observed, and even at an average output of 20 W, the laser processing marks 16 did not reach the intermediate layer 12. It was also found that the depth of the laser processing marks 16 increased as the average laser output increased from 20 W to 32 W.

[0081] Moreover, it was found that the depth of the laser processing marks 16 in the laminate 10 of Comparative Example 3 was 1 μm or more and 29 μm or less, with a difference of about 28 μm. It was also found in Comparative Example 3 that the laser processing marks 16 did not reach the intermediate layer 12 when the average output was 20 W. It was also found that the depth of the laser processing marks 16 increased as the average laser output increased from 20 W to 32 W.

[0082] This confirmed that the configurations of Example 1 and Comparative Example 1 make it possible to form the laser processing marks 16 in a low output range that does not require excessive laser output. Also, it was confirmed that the configuration of Example 1 sufficiently reduces the variation in the depth of the laser processing marks 16 caused by the variation in the average laser output, compared to the configurations of Comparative Examples 1 to 3.

[0083] 6, the breaking strength of the laminate 10 of Example 1 was between 29 N and 35 N, with a difference of only about 6 N. It was also found that the breaking strength decreased slightly as the average laser output increased from 20 W to 32 W, but the decrease was negligible, and it can be said that the breaking strength remained approximately constant with respect to the change in the average output.

[0084] In contrast, the breaking strength of the laminate 10 of Comparative Example 1 was found to be 20 N or more and 60 N or less, with a large difference of about 40 N. The breaking strength of the laminate 10 of Comparative Example 2 was found to be 15 N or more and 73 N or less, with a very large difference of about 58 N. Similarly, the breaking strength of the laminate 10 of Comparative Example 3 was found to be 16 N or more and 101 N or less, with the largest difference of about 85 N.

[0085] This confirmed that the configuration of Example 1 can obtain a low breaking strength suitable for opening in a low output range that does not require excessive laser output. Also, it was confirmed that the configuration of Example 1 sufficiently reduces the fluctuation in breaking strength caused by the fluctuation in average laser output compared to the configurations of Comparative Examples 1 to 3.

[0086] 7, it was confirmed that the width of the laser processing marks 16 in the laminate 10 of Example 1 was 55 μm or more and 102 μm or less, with a difference of about 50 μm. It was also confirmed that the width of the laser processing marks 16 increased as the average laser output increased from 20 W to 32 W.

[0087] On the other hand, it was found that the width of the laser processing marks 16 in the laminate 10 of Comparative Example 1 was also 75 μm or more and 130 μm or less, with a difference of about 55 μm. It was also found that the width of the laser processing marks 16 increased as the average laser output increased from 20 W to 32 W.

[0088] On the other hand, it was found that the width of the laser processing marks 16 in the laminate 10 of Comparative Example 2 was 0 μm or more and 120 μm or less, with a very large difference of about 120 μm.The width of the laser processing marks 16 in the laminate 10 of Comparative Example 3 was 38 μm or more and 70 μm or less, with a difference of about 32 μm. As a result, with the configuration of Example 1, a low breaking strength suitable for opening is obtained, while the fluctuation in breaking strength due to fluctuations in the average laser output is sufficiently mitigated, and it was found that the fluctuation in the width of the laser processing mark 16 was similar to or smaller than those of Comparative Examples 1 and 2.

[0089] 8, the breaking strength of the laminate 10 of Example 1 decreases as the depth of the laser processing marks 16 increases. However, it was found that the magnitude of the weakening of breaking strength per unit depth was smaller than that of any of Comparative Examples 1 to 3. This shows that with the configuration of the laminate 10 of Example 1, the fluctuation in the depth of the laser processing marks 16 caused by fluctuations in the average laser output is sufficiently mitigated, and even if fluctuations do occur, the fluctuation in breaking strength caused by the fluctuation in depth is also sufficiently small.

[0090] 9, the breaking strength of the laminate 10 of Example 1 decreases as the width of the laser processing mark 16 increases. However, it was found that the magnitude of the weakening of the breaking strength per unit size of width was smaller than that of any of Comparative Examples 1 to 3. This shows that with the configuration of the laminate 10 of Example 1, even if the width of the laser processing mark 16 varies due to fluctuations in the average laser output, the variation in breaking strength due to the variation in width is sufficiently small.

[0091] 10, it was found that in the fragile portion 15 of Example 1, the end 16E of the laser processing mark 16 was located midway in the thickness direction of the intermediate layer 12. It was also found that the fragile portion 15 had raised portions 17 that continued in the extension direction of the laser processing mark 16 on both ends in the width direction of the laser processing mark 16.

[0092] As described above, according to the above embodiment, the following effects can be obtained. (1) In a range where the average output is sufficiently low, it is possible to mitigate the variation in the depth of the laser processing marks 16 due to the variation in the laser output. This makes it possible to prevent the laser output from being forced to have an excessively high setting value or an excessively small margin for error in the laser output in order to suppress the variation in the depth of the laser processing marks 16. In addition, it is possible to prevent the occurrence of variation in the depth of the laser processing marks 16 when manufacturing a large number of laminates 10 and packages 20.

[0093] (2) It is possible to improve the reproducibility of preventing the end 16E of the laser processing mark 16 from reaching the sealant layer 13 and remaining inside the intermediate layer 12. This makes it possible to suppress variation in the depth of the laser processing mark 16 when manufacturing a large number of laminates 10 and packages 20, and also to expand the margin of processing error imposed on the sealing of the package 20 and stabilize the sealing performance of the package 20.

[0094] (3) When the proportion of isophthalic acid in the total dicarboxylic acid units of the PET contained in the base layer 11 is 0.5 mol % or more and 5 mol % or less, it is possible to enhance the effectiveness of the effect equivalent to the above (1).

[0095] (4) When the intrinsic viscosity of the PET contained in the base layer 11 is 0.58 dl / g or more and 0.80 dl / g or less, it is possible to provide the base layer 11 with the durability and weather resistance required for the package 20. In addition, when the intrinsic viscosity of the PET contained in the base layer 11 is 0.80 dl / g or less, it is possible to reduce the process load caused by handling of raw materials in the manufacturing process of the base layer 11, such as extrusion, casting, and roll stretching.

[0096] (5) When the width of the laser processing mark 16 expands from the sealant layer 13 toward the first surface 10F, it is easy to irradiate the laser in a direction from the first surface 10F toward the sealant layer 13. In addition, since the presence of the weak portion 15 can be easily recognized from a position facing the first surface 10F, it is also possible to facilitate handling of the weak portion 15 by users of the laminate 10 or the package 20. [Explanation of symbols]

[0097] 10...Laminate 10F…First page 10R…Second side 11...Base material layer 12. Middle class 13…Sealant layer 15…Weakened part 16...Laser processing marks 16E...End 20...Packaging body

Claims

1. A base layer containing chemically recycled polyethylene terephthalate; A laminate comprising: The base layer comprises an outermost surface of the laminate, The laminate includes a weakened portion extending linearly when viewed from a position facing the outermost surface, The fragile portion includes a laser processing mark extending from the outermost surface toward the inside of the laminate. Laminate.

2. Equipped with a printing layer The laminate according to claim 1 .

3. The sealant layer comprises a cyclic olefin copolymer. The laminate according to claim 1 or 2.

4. The sealant layer contains a light blocking agent. The laminate according to any one of claims 1 to 3.

5. The substrate further includes a barrier layer sandwiched between the substrate layer and the sealant layer. The laminate according to any one of claims 1 to 4.

6. The barrier layer includes a vapor-deposited film made of aluminum, aluminum oxide, or silicon oxide, or a resin film containing a saponified ethylene-vinyl acetate copolymer. The laminate according to claim 5.

7. An intermediate layer is further provided between the base layer and the sealant layer, The laser processing mark has an end portion in the thickness direction of the laminate within the intermediate layer. The laminate according to any one of claims 1 to 4.

8. The chemically recycled polyethylene terephthalate contains terephthalic acid and isophthalic acid in the dicarboxylic acid units in the repeating units. A laminate according to any one of claims 1 to 7.

9. The ratio of isophthalic acid to all dicarboxylic acid units of the polyethylene terephthalate contained in the base layer is 0.5 mol % or more and 5 mol % or less. The laminate according to claim 8.

10. The intrinsic viscosity of the polyethylene terephthalate contained in the base layer is 0.58 dl / g or more and 0.80 dl / g or less. The laminate according to any one of claims 1 to 9.

11. The width of the laser processing mark increases from the sealant layer toward the outermost surface. The laminate according to any one of claims 1 to 10.

12. The base layer comprises a first layer made of chemically recycled polyethylene terephthalate and a second layer made of virgin polyethylene terephthalate; The first layer is located closer to the outermost surface than the second layer. A laminate according to any one of claims 1 to 11.

13. A package constructed from the laminate of any one of claims 1 to 12, The sealant layers have a peripheral portion where they are fused together, The fragile portion is disposed at a position on the package intended for opening. packaging.

14. A method for producing a laminate, comprising: irradiating a laser onto a film in which a base layer containing chemically recycled polyethylene terephthalate and a sealant layer having thermoplasticity are laminated, thereby forming a weakened portion in the film, The film is irradiated with the laser from a position facing the base layer. A method for manufacturing a laminate.

15. A method for producing a package, comprising: irradiating a laser onto a film in which a base layer containing chemically recycled polyethylene terephthalate and a sealant layer having thermoplasticity are laminated; forming a fragile portion in the film; and fusing the sealant layers together, The film is irradiated with the laser from a position facing the base layer. A method for manufacturing a package.

Citation Information

Patent Citations

  • Method for reusing recycled pet fiber laminated board, poster using the board, and board for sticking memorandum etc.

    JP2006256102A

  • Easy-to-open pouch

    JP2012214244A

  • Packaging bag for adhesive skin patch

    JP2016040182A

  • Laminate

    JP2017222180A

  • Pillow packing bag

    JP2019218066A